Implementation Of Instagram For Teaching Arabic Reading Skill To Increase Students Learning Motivation - Fitriani, Ismatul Hidayah; Chamidah, Dewi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to analyze the use of Instagram to teach Arabic reading skills (maharah qira’ah), its influence on student learning motivation, and its impact on the learning process. This study uses a quantitative-qualitative approach (mixed method) to obtain comprehensive data. Data was obtained through observations, interviews, and questionnaires to class X Language MAN 2 Malang City, Indonesia, students for the 2023/2024 school year, totalling 34 students. Qualitative data analysis uses the Miles & Huberman model, which involves data collection, reduction, and conclusion. Meanwhile, quantitative data analysis uses the Francis Galton model, which consists of descriptive analysis. The study results show that the use of Instagram as a learning medium has a significant favourable influence on student learning motivation. Instagram features such as interactive visual reels make it easier for students to understand the Arabic reading skill material and increase their interest in actively learning. Students feel more interested because learning is delivered through digital platforms relevant to their interests, so the learning process is fun and effective. As a result, Instagram media has proven effective in increasing students' learning motivation because they are directly involved in learning Arabic reading skills. This study recommends integrating social media such as Instagram as one of the innovative strategies for learning Arabic in the digital era.